Mobile Apps Based on Keller Personalized System of Instruction to Promote English Vocabulary Acquisition - Arumugam, Rooban; Md Noor, Norah (International Journal of Interactive Mobile Technologies (iJIM), 2021)
Mobile learning (or m-learning) is the ability to learn anywhere and at any time using a portable electronic device. Mobile technologies gradually integrate into learnedness. Mobile devices and apps are changing the way learners acquires English. This study aims to develop a mobile Apps based on the Keller Plan Personalized system of instruction (PSI) theory called JuJu English Vocabulary to improve learners’ vocabulary acquisition. The mobile Apps was developed using ADDIE instructional design model. The developed Apps was investigated using a quasi-experimental research design among 60 students separated into two(2) groups: control and experimental groups. Data were analysed using SPSS software. The outcome shows a significant difference between Post-test experimental (using the mobile app) and the control group (traditional learning). This Mobile Apps design allows personalised growth among the experimental group of students in terms of their vocabulary acquisition. The design mimicking a game strategy did help increase their interest to enjoy the learning process.